PENGEMBANGAN SISTEM INFORMASI PEGAWAI BERBASIS WEB DENGAN METODE SCRUM PADA YAYASAN PENYALUR TENAGA KERJA KARYA MULIA - Hamid Mulyadi (OKTAL : Jurnal Ilmu Komputer dan Sains, 2024)
To be able to improve the quality and competitiveness of an uneducated and trained workforce, it is necessary to manage a manpower distribution foundation that is committed to job placement and also educates so that it can become a professional workforce. The labor distribution foundation was established to help people who need workers to take care of housework and help reduce unemployment. The Karya Mulia Foundation is a business entity that specializes in the service sector by distributing a large number of workers to people in need, because labor distributors are obliged to be able to provide the best possible service in distributing labor and processing administrative data. Because this is what the supplier of labor must balance in responding to administrative data processing. The current employee information system is still in the form of a desktop application and has not integrated the data owned by each other so that the accuracy of the workforce information data is not correct and there is a lack of mobility to be able to access or process the data. For this reason, the process of developing a web-based employee information system was carried out with the development methodology used in this research, namely the scrum method. The implementation of this employee information system uses the Java programming language with the Spring Boot framework and the database uses PostgreSQL. Therefore, the results of the study can be concluded that this system is used to obtain employee information data and can also produce work contract transactions and reports.